Low-complexity variable step-size sign algorithm based on Weibull distribution function - Rui ZHANG; Guchen SHI; Banteng LIU; Yourong CHEN (Dianxin kexue)
The performance of the traditional second-order statistics based channel estimation methods degrade seriously in the presence of impulsive noises.In order to deal with this problem,a Weibull distribution function based variable step-size sign algorithm for channel estimation under impulsive noises was proposed.The proposed method was robust against impulsive noises and it could improve the convergence speed of the sign algorithm with the Weibull distribution function based variable step-size method.Computational complexity analysis and simulation results demonstrate that the proposed algorithm can achieve the same steady-state estimation error with faster convergence speed and lower computational complexity.